A disaggregated social accounting matrix: 2010/11 for policy analysis in Egypt - Al-Riffai, Perrihan; Moussa, Suzane; Khalil, Amani; Hussein, Fayza; Serag, Eman; Hassan, Naglaa; Fathy, Ahmed; Samieh, Asmaa; ElSarawy, Mahmoud; Farouk, Embareka; Souliman, Saad; Abdel-Ghafour, Amani (International Food Policy Research Institute, 2016)
The Central Agency for Public Mobilization and Statistics (CAPMAS) is pleased to present a disaggregated version of the Egypt SAM for 2010/11. This new SAM builds on the previous SAM 2010/11 built and published by CAPMAS with the support of the International Food Policy Research Institute (IFPRI). The value added of this new disaggregated version of the SAM is its focus on the agricultural sector and different types of households. By disaggregating the single agricultural sector into 22 agricultural sub-sectors and the single household of the previous SAM into 20 household groups, defined by expenditure decile and rural or urban residence, the disaggregated SAM now allows for analyzing agricultural issues at the detailed crop level and to better understand the potential im-pacts of policy changes for both better off and more vulnerable households.